2016
DOI: 10.1002/jsfa.7715
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofVibrio parahaemolyticusin seafood products from hypermarkets in Shanghai

Abstract: The low prevalence and burden found indicated that seafood from hypermarkets may not be an important risk source for V. parahaemolyticus infection in Shanghai, and more attention should be paid to other areas for selling seafood, such as farmlands or farmers' markets. The simple and effective lognormal distribution is recommended as a better choice for describing V. parahaemolyticus contamination in future risk assessment studies. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…We supposed 8 days as the storage time of refrigerated cooked shrimps, which was referenced from published data. Previous studies suggested the prime quality of shrimps can be retained for 8 days under low temperatures . A beta‐Poisson model was chosen to describe the dose–response relationship between the probability of illness and V. parahaemolyticus : Pi=11+Dγβα …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We supposed 8 days as the storage time of refrigerated cooked shrimps, which was referenced from published data. Previous studies suggested the prime quality of shrimps can be retained for 8 days under low temperatures . A beta‐Poisson model was chosen to describe the dose–response relationship between the probability of illness and V. parahaemolyticus : Pi=11+Dγβα …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested the prime quality of shrimps can be retained for 8 days under low temperatures. 19,21,23 A beta-Poisson model was chosen to describe the dose-response relationship between the probability of illness and V. parahaemolyticus: 24,25…”
Section: Quantitative Microbial Risk Assessmentmentioning
confidence: 99%
“…The researches for V. parahaemolyticus strains isolated from aquatic products are widely reported (Wang et al, 2011; Guo et al, 2013; He et al, 2015, 2016; Lou et al, 2016; Hu and Chen, 2016; Yu et al, 2016; Zhang et al, 2017), while studies on clinical isolates has been poorly documented (Zhang and Orth, 2013; Qi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the majority of clinical V. parahaemolyticus isolates contained the tdh and/or trh gene and have the potential to become a major public health threat (Zhang et al, 2017). However, some environmental V. parahaemolyticus isolates may also possess the tdh and/or trh gene (Xu et al, 2016); therefore, the relationship between the tdh and trh genes and the pathogenicity of V. parahaemolyticus remains unclear.…”
Section: Discussionmentioning
confidence: 99%